Visualizing social acceptance research: A bibliometric review of the social acceptance literature for energy technology and fuels. (June 2018) - Gaede, James; Rowlands, Ian H.
Abstract: This paper conducts content and bibliometric analysis of 857 articles representing the knowledge domain for the social acceptance of energy technology and fuels. The objective is to identify basic trends and characteristics in the literature, identify current research fronts and pivotal papers therein, and map these fronts to their respective intellectual bases. We accomplish this by analyzing metadata, keyword use and citation networks within our dataset. We conclude with an evaluation of influence, structure, and collaboration and interdisciplinary dialogue in the field.